2019
DOI: 10.1093/biolinnean/bly215
|View full text |Cite
|
Sign up to set email alerts
|

Food properties influence grasping strategies in strepsirrhines

Abstract: Although hand grasping is ubiquitous in primate species, its origins remain uncertain. This is in part because uncertainty about hand skills and grasping strategies persists in strepsirrhines, a monophyletic group of primates located near the base of the primate tree. In this study, we report and discuss our observations of the different grasping strategies adopted by 85 captive individuals belonging to 22 species of strepsirrhines during the grasping of food items of different sizes and consistencies. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…For the mobile test procedure, for each species, one food type was chosen from their usual diet in order to maximise the motivation of the species to participate in the experiment (Table 2). A prior study showed that the size, Young's modulus and fracture toughness of the food significantly impact the grasping strategies adopted by strepsirrhines (Peckre et al, 2019). In particular, small items were associated with an increase in mouth grasping compared with strategies involving the hand(s).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…For the mobile test procedure, for each species, one food type was chosen from their usual diet in order to maximise the motivation of the species to participate in the experiment (Table 2). A prior study showed that the size, Young's modulus and fracture toughness of the food significantly impact the grasping strategies adopted by strepsirrhines (Peckre et al, 2019). In particular, small items were associated with an increase in mouth grasping compared with strategies involving the hand(s).…”
Section: Methodsmentioning
confidence: 99%
“…Choosing a relative measure of the size of the item allowed us to control for the high variability of body size across the species tested. As Young's modulus and fracture toughness did not impact small item grasping strategy (Peckre et al, 2019), we examined 21 different small items across a broad range of Young's modulus and fracture toughness values (Table S1). Published data for Young's modulus (median 1.4 MPa, range 0.2-50.4 MPa) and fracture toughness (median 308.6 J m −2 , range 20.0-1030.6 J m −2 ) in a sub-sample of the small items (N=12) indicate a significant positive correlation (r=0.71, P=0.01) between the two material properties (raw data and citations provided in Table S1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations